2022
DOI: 10.1155/2022/4769709
|View full text |Cite|
|
Sign up to set email alerts
|

Phillygenin Protects the Intestinal Barrier from Dysfunction via let-7b Signaling Pathway and Regulation of Intestinal Microbiota

Abstract: The study investigates the positive effects of phillygenin on intestinal tight junction via the let-7b signaling pathway and the regulation of intestinal microbiota. The expression levels of tight junction proteins are determined through PCR and Western blot. DSS-induced mice colitis is used to verify the protective effects of phillygenin on intestinal barrier and tight junction. Fecal microbiota transplantation is used to verify the role intestinal microbiota. let-7b is detected in the colon tissues of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Previous studies have found that Forsythia suspensa Fructus has the potential for treatment of intestinal inflammation 16 . Recently, Feng et al have reported that PHI alleviated dextran sulfate sodium (DSS)‐induced UC through the Nrf2‐NLRP3 pathway and improved metabolic dysfunction 17–19 . In spite of this, the mechanism of PHI in the treatment of UC has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that Forsythia suspensa Fructus has the potential for treatment of intestinal inflammation 16 . Recently, Feng et al have reported that PHI alleviated dextran sulfate sodium (DSS)‐induced UC through the Nrf2‐NLRP3 pathway and improved metabolic dysfunction 17–19 . In spite of this, the mechanism of PHI in the treatment of UC has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Recently, Feng et al have reported that PHI alleviated dextran sulfate sodium (DSS)‐induced UC through the Nrf2‐NLRP3 pathway and improved metabolic dysfunction. 17 , 18 , 19 In spite of this, the mechanism of PHI in the treatment of UC has not been thoroughly studied. In the current study, we performed a more detailed study on the pharmacological impact and mechanism of PHI on colitis.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%